The association between sleep and early pubertal development in Chinese children: a school population-based cross-sectional study - Tang, Jingyi; Yu, Tingting; Jiang, Yanrui; Xue, Peng; Kong, Huijun; Lin, Cuilan; Liu, Shijian; Tian, Ying (Frontiers in Endocrinology, 2023)
Background: There is an increasing tendency toward early pubertal development, and sleep might be related to pubertal onset. We aimed to investigate the association of sleep duration and bedtime with early pubertal development. Methods: This was a cross-sectional study of 8,007 children (53.6% boys) from Qufu city, Shandong province and Zhongshan city, Guangdong province, China. Data on sleep duration and bedtime were obtained by questionnaire. Early pubertal development was the primary outcome, and it was evaluated by the pediatrician according to Tanner staging. Logistic regression models were used to separately examine the association between sleep duration or bedtime and early pubertal development, controlling body mass index (BMI), dietary pattern, soft drink, feeding pattern and mother's BMI. Results: In boys, short sleep duration was strongly related to early pubertal development [OR (95%CI): 4.26 (1.30, 13.94)], and this association was intensified after adjusted BMI, This is a provisional file, not the final typeset article dietary pattern, soft drink, feeding pattern and mother's BMI. In girls, OR (95%CI) was 1.62 (1.04, 2.51), and increased after controlling BMI. Bedtime was associated with early pubertal development on weekdays [OR (95%CI): 6.39 (1.54, 26.45) in boys and 1.93 (1.23, 3.05) in girls], but not on weekends [OR (95%CI): 2.49 (0.61, 10.21) in boys; 1.31 (0.76, 2.25) in girls]. Conclusion: This study underscores the positive association between the risk of early pubertal development and insufficient sleep duration and late bedtime.